2020
DOI: 10.32872/spb.4409
|View full text |Cite
|
Sign up to set email alerts
|

Socially connected and COVID-19 prepared: The influence of sociorelational safety on perceived importance of COVID-19 precautions and trust in government responses

Abstract: COVID-19 caused unprecedented social disruption the likes of which many people had not seen since the Second World War. In order to stop the spread of the virus, most nations were required to enforce strict social distancing precautions, including orders to shelter in place and national lockdowns. However, worries over whether citizens would become fatigued by precautions that constrain personal liberties made some governments hesitant to enact lockdown and social distancing measures early on in the pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
(91 reference statements)
1
6
0
Order By: Relevance
“…Another possibility is that they reported a more negative attitude towards the government's approach because they shifted blame for their burden to the government in an attempt to alleviate COVID-19 related distress (Murray, [unpublished]). Our result is in line with previous research that also showed that higher perceived burden was related to more negative attitudes toward the government [16].…”
Section: Perceived Burden As a Consequence Of The Covid-19 Pandemicsupporting
confidence: 93%
See 1 more Smart Citation
“…Another possibility is that they reported a more negative attitude towards the government's approach because they shifted blame for their burden to the government in an attempt to alleviate COVID-19 related distress (Murray, [unpublished]). Our result is in line with previous research that also showed that higher perceived burden was related to more negative attitudes toward the government [16].…”
Section: Perceived Burden As a Consequence Of The Covid-19 Pandemicsupporting
confidence: 93%
“…In particular, those individuals who perceived the burden to be high may have had more negative attitudes towards the government approach , given the role of the government in putting in place restrictions that were part of the burden that they experienced or that were ineffective at decreasing it. For instance, individuals from the UK who felt that the satisfaction of their need for connectedness was thwarted by the restrictive measures, and thus perceived a greater burden, reported lower trust in their government [ 16 ]. Also, youth who perceived a high burden may also have been more likely to blame certain groups for their negative experiences [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, social networks may represent a crucial resource for resilience and survival in times of crisis, such as the current pandemic situation. Accordingly, greater social connectedness has been found to act as a buffer against perceived stress during the lockdown period (Nitschke et al, 2021) and to influence trust and adherence to governments' safety rules (Lamarche, 2020). However, while gregariousness, i.e., the tendency to seek the company of others, has a beneficial impact on individuals' well-being, it also carries infection-specific risks (Schaller, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Content wise, half of the papers are concerned with specific topics related to working from home, such as security (Pounder 1998;James and Griffiths 2014), process (Guo 2001), work productivity (Higa et al 2000;Lamarche 2020), and inclusion (Ford et al 2019). The other half mostly investigated well-being and productivity while working from home during the pandemic (Ford et al 2021;Ralph et al 2020b;Russo et al 2021a, b;Butler and Jaffe 2021;Machado et al 2021;Smite et al 2021) or productivity-related to projects' characteristics (Bao et al 2020;Cucolas ¸and Russo 2023).…”
Section: Related Workmentioning
confidence: 99%